Inside the EU Code of Conduct Group : 20 Years of Tackling Harmful Tax Competition. - Nouwen, Martijn F. (Amsterdam : IBFD Publications USA, Incorporated, 2021)
This book analyses the functioning and effectiveness of the diplomatic EU Code of Conduct Group in tackling harmful tax competition in the European Union.
Chapter 10 Summary, Conclusions and Outlook: Inside the EU Code of Conduct Group - 20 Years of Tackling Harmful Tax Competition.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Business enterprises--Taxation.; European Union countries; Electronic books